Competitive Factors of Ironworks of Russia in the Short-term Perspective - GOLUBEV, Sergei Sergeevich; SEKERIN, Vladimir Dmitriyevich; GOROKHOVA, Anna Evgenyevna; SIROTKIN, Vladimir Aleksandrovich (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The iron and steel industry is an important branch in Russia and takes a significant position in the international market of metallurgical products. Therefore, the problems of iron and steel companies have significant impact on their competitive ability. It requires the determination of the competitive factors of ironworks for a short-term perspective.